1965
DOI: 10.1136/bmj.1.5446.1352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Calcium upon Serum Lipids in Man

Abstract: Acute Osteitis-Neligan and Elderkin BRIrr hospital. This issue can be obscured by the occasional mild case-commoner in younger children and smaller bones, as described by Bremner and Neligan (1958)-in which delay in terms of days or even weeks may be relatively harmless. In the much commoner severe cases in older children the target period for admission is the first 48 hours after the start of the pain. Then an effective antibiotic will produce a complete cure without any need for local intervention in about 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
1

Year Published

1967
1967
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(35 citation statements)
references
References 13 publications
3
31
1
Order By: Relevance
“…Ten of the 16 hypercholesterolaemic subjects had normal cholesterol level (<200 mg/dL) after 8-weeks calcium supplementation. Denke et al, 10 Yocowitz et al, 11 and Shidfar et al, 13 also reported reduction in TC with calcium supplementation. However, amount reduction (52.4 mg/dL) was a bit higher in the present study when compared with these previous studies; i.e., 6%, 23.6 mg/dL and 28.3 mg/dL respectively.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Ten of the 16 hypercholesterolaemic subjects had normal cholesterol level (<200 mg/dL) after 8-weeks calcium supplementation. Denke et al, 10 Yocowitz et al, 11 and Shidfar et al, 13 also reported reduction in TC with calcium supplementation. However, amount reduction (52.4 mg/dL) was a bit higher in the present study when compared with these previous studies; i.e., 6%, 23.6 mg/dL and 28.3 mg/dL respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Yacowitz et al, reported that there was a mean decrease of 56.3 mg/dL in serum triglyceride level in 11 hypertriglyceridaemic male subjects with calcium carbonate supplementation (0.89 g) for 21 days. 11 Reid et al, reported no significant effect on triglyceride in 108 healthy older men with 1200 mg elemental calcium supplementation for 2 years. 7 In their study, participants consumed a regular-fat diet (about 28% of total calorie intake) and baseline level of triglyceride was 129.21 mg/dL (69.03).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Oral administration of calcium carbonate and other phosphate-binding agents, which reduce intestinal phosphate absorption, are used in CRF to lower the plasma levels of phosphate and PTH (11). Calcium supplementation has also been reported to reduce plasma cholesterol levels, probably because orally ingested calcium binds bile acids and saturated fatty acids in the intestine (14,34,37). Elevated plasma cholesterol level is known to be associated with impaired endothelial function in both humans (6) and in rats (10,18,21).…”
mentioning
confidence: 99%